2012
DOI: 10.1007/s11199-012-0232-5
|View full text |Cite
|
Sign up to set email alerts
|

Benevolent Sexism, Men’s Advantages and the Prescription of Warmth to Women

Abstract: Gender prescriptions consist of beliefs about the characteristics that men and women should possess. This paper focuses on stereotypic prescriptions targeting women and on some of the variables that influence the adherence to these prescriptions. In Study 1, male undergraduates (N036) from Belgium completed the Ambivalent Sexism Inventory (ASI-Glick and Fiske 1996), questions assessing the prescription of warmth-and competence-related traits to a female target and a measure of the target's perceived status. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 70 publications
1
15
0
1
Order By: Relevance
“…Es necesario, por tanto, estimular el reparto equilibrado de las responsabilidades familiares para romper con estereotipos de género, tan unidos al mantenimiento del sexismo. Aunque el SB es aparentemente más conciliador, también es más eficaz para perpetuar diferencias de género (Delacollette, Dumont, Sarlet, & Dardenne, 2013).…”
Section: Discussionunclassified
“…Es necesario, por tanto, estimular el reparto equilibrado de las responsabilidades familiares para romper con estereotipos de género, tan unidos al mantenimiento del sexismo. Aunque el SB es aparentemente más conciliador, también es más eficaz para perpetuar diferencias de género (Delacollette, Dumont, Sarlet, & Dardenne, 2013).…”
Section: Discussionunclassified
“…But warmth prescription for women is also a function of the context: Warmth traits were more prescribed for them in a private than in a work context (Delacollette, Dumont, Sarlet, & Dardenne, 2012). In our studies, we demonstrated that protective paternalism is prescribed for men, particularly in a romantic context and particularly if women endorsed higher levels of Protective Paternalism and Heterosexual Intimacy.…”
Section: Discussionmentioning
confidence: 99%
“…Critically, the warmth/trustworthiness expectations contained within BS are prescriptive in nature; women and men “ought to” and “should be” warm, sensitive, supportive, and loyal (Delacollette, Dumont, Sarlet, & Dardenne, ; Sarlet et al, ). Such prescriptions create strong boundaries of how men and women should and should not be or behave (Burgess & Borgida, ).…”
Section: Bs and Ideal Standards For Relationship Partnersmentioning
confidence: 99%